S131. Reducing glucose variability with continuous subcutaneous insulin infusion is associated with reversal of axonal dysfunction in type 1 diabetes mellitus. (May 2018) - Kamel, Jordan; Loh, Margaret; Cook, Mark; MacIsaac, Richard; Roberts, Leslie
Abstract : Introduction: Strict glycaemic control has been shown to reduce the risk of developing peripheral neuropathy in patients with type 1 diabetes mellitus (T1DM). Continuous subcutaneous insulin infusions (CSII) can provide improved diabetes control by reducing both mean glucose and glucose variability (GV). This could potentially reverse functional changes in neuronal membrane ion channels and pumps that occur prior to the onset of permanent nerve damage, and thus prevent the fatal cascade that leads to axonal death. Methods: 12 patients with T1DM treated with multiple daily insulin injections (MDII) were assessed with nerve excitability testing prior to, and three months following initiation of CSII. Blood glucose, HbA1c and GV measured using a continuous glucose monitor (CGM) were correlated with changes in nerve excitability parameters. Results: Overall, simply commencing treatment with CSII for three months did not significantly alter any nerve excitability parameter or GV, although HbA1c improved. In four patients, some deterioration in GV was observed, whilst eight patients had improvement in standard deviation (SD) and mean amplitude of glycaemic excursions (MAGE). For these eight patients, there was normalisation of depolarising and hyperpolarising threshold electrotonus and recovery cycle superexcitablity. Standard deviation of CGM readings correlated with all these parameters. Conclusion: The initiation of CSII in patients with T1DM does not ensure a neuroprotective effect in itself, but when it is successful in reducing GV, there is reversal of axonal dysfunction. The pattern of nerve excitability improvement seen is most consistent with restoration of transaxonal membrane potential due to normalisation of Na+/K+ pump function.